MOSQUITO REPELLANT MODELS USED IN DRUG DISCOVERY - Mittal, Payal; Gupta, Vikas; Kaur, Gunpreet; Goswami, Manish; Thakur, Nishant; Singh, Amarpreet (Journal of Biomedical and Pharmaceutical Research, 2017)
Vector-borne diseases are infections transmitted by the bite of infected arthropod species, such as mosquitoes, ticks, triatomine bugs, sandflies and blackflies. Mosquitoes are the most important insects which transmit a number of diseases such as dengue, chikungunya, filariasis, malaria and cause millions of deaths every year. An alarming increase in the range of mosquitoes is mainly due to deforestation, industrialized farming and stagnant water. Mosquito control and personal protection from mosquito bites are currently the most important measures to prevent these diseases. The use of mosquito repellent compounds dates back to antiquity. Insect repellents work by masking human scent. There are many types of mosquito repellents commercially available in market but these products have varying degrees of effectiveness. Purpose of this compilation is to bring all the methods at a single platform so as to enable scientists working on these repellents to know the scientific clues available in literature. The compilation reflects that there is no such method that is best for mosquito repellent as every method has drawbacks. So, there is a need to search such mosquito repellent product/ method for combating mosquitoes. Keywords: Repellents, Mosquitoes, Vector-borne diseases